ESTABLISHING THE MECHANISM OF MANDIBULAR FRACTURES (World Bulletin of Public Health, 2024)
The article covers the characterization of the mechanisms of mandibular fractures. According to the results, it is established that the mandible, having an arc-shaped form, under mechanical impact experiences bone tissue stress in the most curved or thinnest parts of the mandible. Such areas within the mandible are the base and neck of the condyle, the angle, the area of the chin opening and canine, and the chin section. It is in these most "weak" places that the mandible breaks due to its bending. Various variants of mandibular fracture are possible
Keywords: Mandible; fractures; mechanism; characteristic